Switching Cost to Customer Loyalty: Operation and Business Relationship - Puji Setyawan E. Putranto (Business and Entrepreneurial Review, 2005)
Many business customers to day consolidate their supply basis and implementing preferred supplier programs. Consequently suppliers forced to gain a key supplier status from their customers where as a collaborative buyer-seller relationship represents a source of competitive advance. The vendors sometimes in flict switching costs on their customers, to prevent them from defecting to new suppliers. In a competitive setting where competition dominated by a price war, the potential switching costs might be an exit barrier and a binding factor of customer loyalty. ln efforts to address that issue this research examines the moderating effects of switching costs on customer loyalty through both satisfaction and perceived-value measures. The research investigates opporlunities for differentiation through value creation in business to business (B2B) relationship.